2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.538
|View full text |Cite
|
Sign up to set email alerts
|

E-Business IT Governance Revisited: An Attempt towards Outlining a Novel Bi-directional Business/IT Alignment in COBIT5

Abstract: In contrast to classical business, e-business highly depends on internet technologies. Business and IT naturally coalesce here. Thus, a customerdriven IT requirement may enforce an adjustment of a business model. This poses new challenges for researchers and practitioners as currently a business-driven alignment paradigm dominates in IT governance. We identify characteristics of e-business and examine how IT governance frameworks can integrate these characteristics under consideration of a bi-directional busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Though, the significance and degree/approach of consideration of specialized requirements as for example issued in earlier work by Bartens et al [44] (i.e. differentiations in process concretization) or scope limitations and restrictions as set by COBIT 4.1 Quickstart [43] (i.e., enterprise branch and size, degree of IT dependency/intensity) or this paper, remain not yet addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Though, the significance and degree/approach of consideration of specialized requirements as for example issued in earlier work by Bartens et al [44] (i.e. differentiations in process concretization) or scope limitations and restrictions as set by COBIT 4.1 Quickstart [43] (i.e., enterprise branch and size, degree of IT dependency/intensity) or this paper, remain not yet addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The main difference for this paper is its special emphasis on the detailed process level of innovation and change management which is its sole contribution to the literature. Bartens et al (2014) identified characteristics of ebusiness and examine how IT governance frameworks can integrate these characteristics under consideration of a bi-directional business/IT alignment process using COBIT 5 as a benchmark. Shalamanov (2017) attempted to structure the experience as a methodology to support institution building and change management in similar servicebased or technology-oriented organizations.…”
Section: Literature and Methodsmentioning
confidence: 99%
“…IT governance is a framework that enables organizations to manage their information resources efficiently and effectively and helps them in achieving their enterprise objectives. Major areas to be addressed by IT governance are: meeting IT expectations, alignment of IT with business and mitigating the IT risks [26]. The five key focus areas of IT governance are given below:…”
Section: It Security Governancementioning
confidence: 99%